Association between polymorphisms in microRNAs and susceptibility to diabetes mellitus: A meta-analysis - Chen, Xi (Medicine (Baltimore), 2019)
BACKGROUND: Accumulated evidence has indicated the associations between single-nucleotide polymorphisms (SNPs) in microRNAs (miRNAs) and the susceptibility to diabetes mellitus (DM), but the conclusions remain controversial. This study was to investigate the true contribution of miRNA SNPs to the risk of DM by using a meta-analysis of all the published studies. METHODS: Relevant studies were identified in the databases of PubMed and the Cochrane Library databases. The strength of associations between miRNA polymorphisms and DM risk was assessed by odds ratios (ORs) and 95% confidence intervals (95% CIs) under five genetic models using the STATA software. RESULTS: Six studies, containing 2773 cases and 2632 controls, were enrolled, 5 of which evaluated miR-146a (rs2910164), 4 for miR-27a (rs895819), and 3 for miR-124 (rs531564) and 2 for miR-375 (rs6715345), miR-128a (rs11888095), miR-194a (rs3820455). The meta-analysis indicated that the G allele or GG genotype of miR-146a rs2910164 was associated with a significantly increased risk for DM compared with C allele or GC/CC genotype in Latin American population; CC genotype of miR-27a rs895819 polymorphism was associated with a significantly decreased risk for DM in Asian population compared with the TT genotype; patients carrying with CC genotype of miR-124 rs531564 had a lower probability to develop DM regardless of ethnicity; no associations were identified between polymorphisms in miR-375, miR-128a, miR-194a and the susceptibility to DM. CONCLUSION: Our study suggests that miR-146a/miR-27a and miR-124 polymorphisms may be ethnicity-dependent or -independent susceptibility factors to DM, respectively.